Protecting our environment recycle (California : AIMS Multimedia, 1997)
Back to basics CD-ROM series contains: complete linear video, interactive quiz with video reinforcement, bulletin board, glossary, test with record keeping, teacher management system.
Keywords: Recycling (Waste, etc.) -- Study and teaching; Pollution -- Study and teaching